The qualitiy of the tourist destinations a key factor for increasing their attractiveness - Daliborka Blazeska; Ace Milenkovski; Sashko Gramatnikovski (UTMS Journal of Economics, 2015)
Taking into consideration that the tourism is extremely important for any country including Republic of Macedonia, it is necessary to pay attention to the quality of the tourist destinations and increasing of their attractiveness. So winners in the field of tourism will be those countries that have attractive tourist destination that will attract a lot of visitors. In this paper is defined the relationship between the factors of attractiveness of the destination and the achieving of competitiveness. In order to become competitive in the global market, the tourist destination has to be innovative and to continually search for new competitive advantages. Those kind of competitive advantages enable stable and long-term sustainable development of the tourist destination. In this paper special emphasis is put to the monitoring of the quality of the tourist destination with constant inquiries of the tourists (domestic and foreign) regarding the most important segments of the quality of the tourist product which they are using, in order to perceive the satisfaction or the eventual dissatisfaction in order to be taken concrete strategies for the following period. The obtained results clearly confirm the dissatisfaction with the road infrastructure and signalization, the price of the services and the conditions for the stay, as well as the additional attractions that were expected to get.
Keywords: Q01; M30; 330; quality; tourist product; tourist destinations; attractiveness; satisfaction of the consumers